A SOCIO-ETHICAL AND PHILOSOPHICAL ANALYSIS OF THE PARADIGM OF PEACE IN THE AVESTA - Sharipov, Dilshod (Journal of Research and Development, 2026)
This article examines the paradigm of peace in the Avesta from social, ethical, and philosophical perspectives. The aim of the study is to elucidate the content of the concept of peace in Zoroastrian doctrine and to determine its role in shaping the relationships between human beings, society, and nature. The research employs historical-philosophical analysis, a comparative approach, and textual source analysis. The findings indicate that in the Avesta, peace is conceptualized as a comprehensive ethical system grounded in the principles of good intention, good thought, good speech, and good action. Within this framework, spiritual development of the individual, attitudes toward labor, the institution of the family, and harmony with nature are identified as key determinants of peace. Furthermore, the dualistic struggle between good and evil is presented as a fundamental factor shaping human moral choice. It is concluded that the concept of peace articulated in the Avesta constitutes a significant theoretical foundation for promoting sustainable development and social harmony in contemporary society.